Review Article: The Flagship of Evidence-Based Medicine - Lazarides, Miltos K; Lazaridou, Irene-Zacharo; Papanas, Nikolaos (International journal of lower extremity wounds, 2021)
Global literature is ever-growing and physicians rely on it for evidence-based decision making. Review articles summarize available literature and provide the current state of knowledge on a given topic. Various review types exist, the main ones being narrative and systematic reviews. The former are based on studies selected in an undefined manner. They express the authors' opinions of a given topic, lack a systematic search, and are prone to bias. By contrast, the latter represent an unbiased synthesis of knowledge on a particular topic and attempt to offer all relevant evidence. A systematic review may include a meta-analysis, which combines the results of quantitative studies using statistical techniques to provide a more precise summary of the evidence. With a dramatic increase in literature complexity, new "next-generation" types of reviews emerged to improve the quality of evidence synthesis: network meta-analysis, umbrella review, and meta-analysis of individual patient data, among others. Finally, scoping reviews are a special type, conducted as precursors to systematic reviews aiming to reveal specific knowledge gaps in a given subject.